2023
DOI: 10.1097/crd.0000000000000575
|View full text |Cite
|
Sign up to set email alerts
|

Red Meat Consumption and its Relationship With Cardiovascular Health: A Review of Pathophysiology and Literature

Abstract: Red meat is the muscle meat of mammals like beef, lamb, and pork that is red due to the abundance of myoglobin pigment and becomes even darker when cooked. The global average per capita consumption of meat and the total amount of meat consumed is rising, and there has been a particularly marked increase in the global consumption of chicken and pork. The consumption of red meat has always been a contentious issue, with data suggesting benefits in terms of nutritional value and at the same time linking its consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Strategies to improve access to fresh vegetables, especially in comparison to meat and fast food outlets, are being explored to promote better nutrition and health outcomes across different communities [114]. Epidemiological studies have indicated that regular and high intake of red meat may be associated with accelerated aging processes and an increased risk of age-related diseases [115][116][117][118][119][120][121][122][123][124][125][126][127]. Of particular concern is the relationship between red meat consumption and cardiovascular and cerebrovascular diseases [120,121,123,[127][128][129][130][131][132][133][134][135][136][137].…”
Section: Dietary Sources Of Methioninementioning
confidence: 99%
See 1 more Smart Citation
“…Strategies to improve access to fresh vegetables, especially in comparison to meat and fast food outlets, are being explored to promote better nutrition and health outcomes across different communities [114]. Epidemiological studies have indicated that regular and high intake of red meat may be associated with accelerated aging processes and an increased risk of age-related diseases [115][116][117][118][119][120][121][122][123][124][125][126][127]. Of particular concern is the relationship between red meat consumption and cardiovascular and cerebrovascular diseases [120,121,123,[127][128][129][130][131][132][133][134][135][136][137].…”
Section: Dietary Sources Of Methioninementioning
confidence: 99%
“…Epidemiological studies have indicated that regular and high intake of red meat may be associated with accelerated aging processes and an increased risk of age-related diseases [115][116][117][118][119][120][121][122][123][124][125][126][127]. Of particular concern is the relationship between red meat consumption and cardiovascular and cerebrovascular diseases [120,121,123,[127][128][129][130][131][132][133][134][135][136][137]. The potential adverse effects on health of red meat consumption have been attributed to an increased intake of cholesterol, saturated fat, and methionine [128][129][130][131][132][133][134][135][136][137].…”
Section: Dietary Sources Of Methioninementioning
confidence: 99%
“…Yet pork meat is largely missing from the global nutrition and sustainability discourse and is rarely mentioned in the Dietary Guidelines for Americans [ 11 ]. Rather, pork meat in both research and policy documents is typically assigned to the category of red meat [ 12 , 13 ]. As attention turns to the forthcoming United States Dietary Guidelines 2025–2030, it is important to separate pork meat from other protein sources and from other meats, where existing data allow.…”
Section: Introductionmentioning
confidence: 99%
“…Pooling pork, beef, and lamb is very common in nutrition and epidemiology research [ [12] , [13] , [14] , [15] ]. Food frequency questionnaires often used to support public health policy, typically bundle pork with beef and lamb.…”
Section: Introductionmentioning
confidence: 99%
“…Pork is the most widely consumed meat in the world and plays a crucial role in ensuring global food security [1,2]. The deposition and composition of lipids in pork affect its sensory and nutritional quality, with triglycerides (TG) being the main form of lipid storage [3].…”
Section: Introductionmentioning
confidence: 99%